Pharmacologically-induced stress has minimal impact on judgement and attention biases in sheep - Monk, Jessica E. (Sci Rep, 2019)
The emotional impact of exposure to stressors has not been well quantified in animals. We hypothesised that exogenous induction of stress in sheep would induce a pessimistic judgement bias and increased attention towards a threatening stimulus, suggestive of a negative emotional state. Stress was induced pharmacologically by administering synthetic adrenocorticotropic hormone. Judgement bias was assessed using a spatial go/no-go task after exposure to acute stress (one injection), chronic stress (21 daily injections) and acute-on-chronic stress (2 min isolation after 28 daily injections). Attention bias was assessed during chronic stress only (22 daily injections). In contrast with our hypotheses, there was no strong evidence that Synacthen administration altered judgement bias or attention bias at any stage of the experiment. Stressed sheep were more likely to approach ambiguous locations than saline Control animals, however, statistical evidence for models fitting treatment group was very weak. Overall, our findings suggest that elevated levels of cortisol may not fully explain changes to judgement bias observed in previous studies after environmentally-induced stress. Further studies are required to better understand which aspects of environmentally-induced stress alter judgement bias and to further validate cognitive methods of assessing affect in sheep.